2020
DOI: 10.1007/s11085-020-09959-6
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation in Air at 1400 K and Optical Properties of Inconel 625, FeCrAlloy and Kanthal Super ER

Abstract: The materials used for the design of the solar receiver are one of the critical parts of the concentrated solar power (CSP) plants. An increase of the working temperature of the solar receiver could induce an increase of the efficiency of the CSP plants. Historically stainless steels were used for the solar receiver. However one limit of these materials is their poor creep resistance at high temperature. Nowadays Ni-based alloys are used, but they are limited at 1400 K by their oxidation resistance. Thus, to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…However, for samples heated above 750 °C, apart from the CMO signatures, many other peaks are visible. The main Inconel 625 peaks seen in the as-prepared cases split and became multiple peaks, suggesting that the Inconel substrate degraded to many other phases and oxides of Cr, Ni, Fe, Mo, etc., as seen in the EDS spectra . Therefore, substrate oxidation, particularly above 750 °C, is relevant to these tests.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…However, for samples heated above 750 °C, apart from the CMO signatures, many other peaks are visible. The main Inconel 625 peaks seen in the as-prepared cases split and became multiple peaks, suggesting that the Inconel substrate degraded to many other phases and oxides of Cr, Ni, Fe, Mo, etc., as seen in the EDS spectra . Therefore, substrate oxidation, particularly above 750 °C, is relevant to these tests.…”
Section: Resultsmentioning
confidence: 97%
“…The main Inconel 625 peaks seen in the as-prepared cases split and became multiple peaks, suggesting that the Inconel substrate degraded to many other phases and oxides of Cr, Ni, Fe, Mo, etc., as seen in the EDS spectra. 54 Therefore, substrate oxidation, particularly above 750 °C, is relevant to these tests. Many researchers have also reported that above 750 °C, there is significant cation diffusion from the Inconel 625 substrate to the coating, resulting in the formation of nickel and chromium at the interfaces.…”
Section: Structural Study Figures 6a and 6bmentioning
confidence: 99%
“…An 18 mm diameter cylinder was cut into several disks whose thicknesses range from 2 to 3 mm. These disks were polished in order to reach a quadratic surface roughness between 0.5 and 0.8 µm, with the procedure previously described [24].…”
Section: Methodsmentioning
confidence: 99%
“…Oxidation performed at 1770 K in synthetic air has shown the formation of a protective oxide scale after up to 168 h oxidation time [23]. In a previous work [24], the oxidation kinetics and room temperature optical properties of the currently used Inconel 625 have been compared to those of the alternative alloys FeCrAlloy and Kanthal Super ER (KSER) and this latest one supported 48 h oxidation at 1373 K in air inside a muffle furnace with the weakest weight change.…”
Section: Introductionmentioning
confidence: 99%
“…The maximum operating temperature of the polycrystalline nickel-based alloys currently used in the design of industrial solar receivers is approximately 800 °C when 100,000 hours of use are considered [3]. In fact, previous investigations have revealed that Inconel 625 cannot withstand more than 36 h of exposure to air at 900 °C before oxide scale spallation occurs [4].…”
Section: Introductionmentioning
confidence: 99%